Hubungan Praktik Penggunaan APD dan Karakteristik Individu dengan Keluhan Gangguan Pernapasan pada Pemulung di TPA Sanggrahan Kabupaten Temanggung - Prasetiyawati, Ida; Suhartono, Suhartono; Setiani, Onny (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
Sanggrahan landfill is an area used as place to collect solid waste in Temanggung Regency. The existence of a landfill to reduce waste accumulation in the environment, but on the other side a landfill can cause a problem like air pollution caused by waste decomposition. Waste pickers in the landfill have a risk respiratory disorder as a result of exposure to air pollutants. The purpose of this study was to analyze association between the use of personal protective equipment (PPE) and individual characteristics with respiratory disorders on waste pickers at Sanggrahan landfill. The type of this study was an observational analitical using a cross sectional approach. Subjects involved in this reseach were 69 waste pickers and were taken by using total sampling technique. The results showed that there were 68,12% waste pickers suffered complaints of respiratory disorder, the most of them having cough 43,4%, flu 47,8% and fever 27,5%. Chi square analyze showed that there were no association between gender(p=0,464), age (p=0,206), education (p=0,318), and smoking habit (p=0,585) with complaints of respiratory disorder. While, there were association between the working hours (p=0,039), length ofwork(p=0,025), use of PPE(p=0,0019), and the use of respiratory protective equipment (p=0,021) with complaints of respiratory disorder. It is expected that waste pickers can use full PPE such as a hats, long clothes, gloves, foot protection, and standard mask during their working activites or while working in the landfill area.